2020
DOI: 10.1177/0003702819881215
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Carbon Monoxide Two-Photon Laser-Induced Fluorescence (LIF) Spectra at High Temperature and Pressure

Abstract: In this study, quantitative model of two-photon excitation and fluorescence spectra of carbon monoxide based on up-to-date spectroscopic constants collected during an extensive literature survey was developed. This semi-classical model takes into account Hönl–London factors, quenching effects (collisional broadening and shift), ionization and stark effect (broadening and shift), whereas predissociation is neglected. It was specifically developed to first reproduce with a high confidence level the behavior of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…is obtained. The uncertainty is caused to a large extend by the two-photon excitation cross section of Di Rosa and Farrow [25] that is nowadays still the commonly used one [15]. Beside the uncertainty on σ (2) , as anticipated in section 3.1, the two-photon nature of TALIF requires particular care in the estimation of ε p , F (t) and Ã, since differences with respect to the real, i.e.…”
Section: Determination Of the Calibration Constantmentioning
confidence: 99%
See 1 more Smart Citation
“…is obtained. The uncertainty is caused to a large extend by the two-photon excitation cross section of Di Rosa and Farrow [25] that is nowadays still the commonly used one [15]. Beside the uncertainty on σ (2) , as anticipated in section 3.1, the two-photon nature of TALIF requires particular care in the estimation of ε p , F (t) and Ã, since differences with respect to the real, i.e.…”
Section: Determination Of the Calibration Constantmentioning
confidence: 99%
“…With a proper calibration, absolute number densities can be determined with high temporal and spatial resolution [14]. The detection of CO with two-photon absorption laser-induced fluorescence (TALIF) spectroscopy is common practice in combustion research [15,16] but has also been shown to be applicable in CO 2 plasma conversion studies [17].…”
Section: Introductionmentioning
confidence: 99%